Tracing the Animal in the Human: Review of Christopher Peterson, Bestial Traces: Race, Animality and Sexuality - Diamond-Lenow, Chloe (Humanimalia, 2015)
Christopher Peterson. Bestial Traces: Race, Sexuality, Animality. New York: Fordham University Press, 2013. 208 pp. 75 hc, 24 pb.